NEW MYOKIN IRIZIN: PHYSIOLOGICAL AND PATHOPHYSIOLOGICAL ROLE - Novoskoltcev, A. (The Ukrainian Scientific Medical Youth Journal, 2018)
New mechanisms of influence of physical activity on the human body are investigated nowadays, one of which is secretion of peptide hormone irisin. After physical examinations PGC-1α is synthesized in muscles and stimulates expression of FNDC5 that after modification is secreted as irisin. The recent scientific researches show that irisin plays an important role in energy and metabolic processes in organism. The data about regulation of synthesis, main functions and mechanisms of action, clinical signification of hormone irisin in conditions of physical activity are covered in present review.